1981
DOI: 10.1083/jcb.89.2.373
|View full text |Cite
|
Sign up to set email alerts
|

Decoration of spindle microtubules with Dynein: evidence for uniform polarity.

Abstract: Studies were conducted to determine whether the microtubules present within native spindles isolated from eggs of the surf clam, Spisula solidissima, could bind dynein obtained from axonemes of Tetrahymena thermophila . SDS gel electrophoresis revealed that the high molecular weight polypeptides that make up dynein cosedimented with the isolated spindles . Moreover, the ATPase activity of dynein bound to the spindle microtubules was stimulated approximately sevenfold . The birefringence retardation of spindles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(59 citation statements)
references
References 44 publications
4
55
0
Order By: Relevance
“…4a). B-end binding is characterized by an electron-transparent gap separating the dynein arm from the wall of the microtubule [Telzer and Haimo, 1981;Haimo and Fenton, 19841. In contrast, when dynein was added to a preparation of preassembled microtubules, the arms bound preferentially by their A ends (Fig.…”
Section: Characteristics Of the Binding Of The Two Ends Of The Dyneinmentioning
confidence: 99%
See 1 more Smart Citation
“…4a). B-end binding is characterized by an electron-transparent gap separating the dynein arm from the wall of the microtubule [Telzer and Haimo, 1981;Haimo and Fenton, 19841. In contrast, when dynein was added to a preparation of preassembled microtubules, the arms bound preferentially by their A ends (Fig.…”
Section: Characteristics Of the Binding Of The Two Ends Of The Dyneinmentioning
confidence: 99%
“…4b), even with dynein present in excess to saturate the microtubules. A-end binding is characterized by the direct attachment of the arm to the wall of the microtubule [Telzer and Haimo, 1981;Haimo and Fenton, 19841. There are three possible explanations for the preferential attachment of the B end of the arm to microtu- Mass ratio values represent the mean f standard deviation for the ratio of the sum of the areas under the dynein heavy-chain peaks to the sum of the areas under the a and 0 tubulin peaks. ATPhanadate:…”
Section: Characteristics Of the Binding Of The Two Ends Of The Dyneinmentioning
confidence: 99%
“…appear in traditional thin-section images (2). The "A end" (65) of the arm is depicted as a straight component that extends diagonally outward from the A microtubule, and the "B end" is represented as a larger hook-shaped component that extends towards the B microtubule of the adjacent doublet. The B end does not ordinarily appear to make contact with the B microtubule, leaving an interdoublet "gap.…”
Section: Sample Size and Consideration Of Artifactsmentioning
confidence: 99%
“…There have been numerous reports on the presence of dynein ATPase and dyneinlike ATPase activities in the mitotic apparatus of dividing ceils (see Pratt et al, reference 28, for example and brief review) as well as identification by histochemical methods of ATPase activity on microtubules in situ in nerve ceils (30). In addition, the finding that exogenous dynein from flagella binds to brain microtubules with the same periodicity found in axonemes (15) and that dynein from cilia binds to spindle microtubules (35) has suggested that dynein may function in association with cytoplasmic microtubules (16,23). On the basis of these observations it has been proposed that the force-generating molecules for motility may be endogenous, microtubule-based proteins such as dynein or other associated proteins with ATPase activity.…”
mentioning
confidence: 99%